2017
DOI: 10.1080/10888438.2017.1320402
|View full text |Cite
|
Sign up to set email alerts
|

Early Indicators of Later English Reading Comprehension Outcomes Among Children From Spanish-Speaking Homes

Abstract: In this longitudinal study, we examined the relationship between primary grade (K-2) Spanish and English language- and word-based skills and later English reading comprehension (RC) outcomes (Grades 5 and 8) among children (n = 148) from immigrant, Spanish-speaking, low-income homes in English instructional contexts since Kindergarten entry. As expected, early skills, especially those in English, contributed to later RC outcomes. Most uniquely, we identified a developmental shift in the contribution of languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
47
1
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 36 publications
7
47
1
3
Order By: Relevance
“…If the articles in this special issue share one central theme, it is that student‐ and setting‐level characteristics must inform an approach to identifying and supporting ELs at‐risk for reading difficulties. Moreover, consistent with a robust research base with English‐only speakers, they also highlight how EL‐specific risk profiles, or “early warning indicators,” such as low performance on measures of oral language development in English at the start of kindergarten, might offer a promising approach to identification (Francis et al., this issue; Mancilla‐Martinez & Lesaux, ; Rojas, Hiebert, Gusewski, & Francis, this issue). Indeed, without targeted and intensive efforts, low oral language at kindergarten entry is likely to persist and ultimately negatively impact reading comprehension.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…If the articles in this special issue share one central theme, it is that student‐ and setting‐level characteristics must inform an approach to identifying and supporting ELs at‐risk for reading difficulties. Moreover, consistent with a robust research base with English‐only speakers, they also highlight how EL‐specific risk profiles, or “early warning indicators,” such as low performance on measures of oral language development in English at the start of kindergarten, might offer a promising approach to identification (Francis et al., this issue; Mancilla‐Martinez & Lesaux, ; Rojas, Hiebert, Gusewski, & Francis, this issue). Indeed, without targeted and intensive efforts, low oral language at kindergarten entry is likely to persist and ultimately negatively impact reading comprehension.…”
mentioning
confidence: 54%
“…The three remaining studies define their at‐risk readers by examining these foundational word‐level skills—including PA and other code‐based skills—as well as meaning‐based competencies. Research indicates that meaning‐based competencies, which include comprehension skills and vocabulary knowledge, must be developed over many years and are key sources of lasting individual differences in reading ability, especially among ELs (e.g., Mancilla‐Martinez & Lesaux, ; Mancilla‐Martinez & Lesaux, ; Snow & Uccelli, ). To that end, in their efforts to identify the evidence‐based instructional practices that best support at‐risk ELs, Hall, Steinle, and Vaughn explore the importance of both code‐ and meaning‐based skills in detail and in the context of instruction.…”
mentioning
confidence: 99%
“…Yet, the school‐age population of nonnative English speakers is growing rapidly (National Center for Education Statistics, ; McFarland et al., ), and databases reveal a main effect, in which nonnative English speakers’ math and reading performance falls substantially below that of native English speakers (National Center for Education Statistics, ). Moreover, in this population, studies document the relation of vocabulary and/or syntax with word‐problem solving (e.g., Foster, Anthony, Zucker, & Branum‐Martin, ; Méndez, Hammer, Lopez, & Blair, ) and reading comprehension (Mancilla‐Martinez & Lesaux, ; Nakamoto, Lindsey, & Manis, ; Proctor, Carlo, August, & Snow, ).…”
Section: Exploratory Hypotheses and Development Of A Neuroimaging Parmentioning
confidence: 99%
“…By using a quantile regression approach, recent studies have revealed that explanatory factors can vary across the range of word reading ability (McIlraith & LRRC, 2016) and reading comprehension ability (Hua & Keenan;LRRC & Logan, 2017;Mancilla-Martinez & Lesaux, 2017;Tighe & Schatschneider, 2016). Hua and Keenan (2017) showed that for several reading comprehension tests, the contribution of word decoding skills and listening comprehension varied as a function of reading comprehension ability in younger and older readers (8-18 years).…”
Section: Reading Comprehension Across the Distributionmentioning
confidence: 99%
“…It was concluded that quantile regression is a useful approach for the study of reading in both typical and atypical readers. With respect to the latter, there is one quantile regression study with only L2 readers showing that the relation between early language skills and later reading comprehension outcomes was stronger for L2 readers with higher ability levels (Mancilla-Martinez & Lesaux, 2017).…”
Section: Reading Comprehension Across the Distributionmentioning
confidence: 99%